1992
DOI: 10.1097/00006254-199208000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Studies of Human Birthweight From the 1958 Birth Cohort. 1. Evidence for a Multigenerational Effect

Abstract: Objective To ascertain whether maternal twinning influences the previously described association between the birthweight of singleton mothers and their infants. Design and subjects The association between the birthweight of singleton parents and their offspring and that between twin parents and their offspring was compared using data from the 23‐year‐old sample of the 1958 British national birth cohort. The numbers available for full comparison were 1027 female and 611 male singleton cohort members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
3
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 0 publications
7
107
3
1
Order By: Relevance
“…While intergenerational effects on human BW have been extensively studied in developed nations, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21] there is a paucity of data from developing countries. 17,22 Strengths of the present study were a large sample size, birth data were collected prospectively for the parental cohort (for whom birth measurements were taken by trained research staff), birth data of the offspring were obtained only from reliable hospital records (rather than recall) and we had good data on potential confounding factors such as parental age, height, weight, sex of infant, birth order and SES.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While intergenerational effects on human BW have been extensively studied in developed nations, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21] there is a paucity of data from developing countries. 17,22 Strengths of the present study were a large sample size, birth data were collected prospectively for the parental cohort (for whom birth measurements were taken by trained research staff), birth data of the offspring were obtained only from reliable hospital records (rather than recall) and we had good data on potential confounding factors such as parental age, height, weight, sex of infant, birth order and SES.…”
Section: Discussionmentioning
confidence: 99%
“…The father's contribution is mainly genetic [6][7][8][9][10][11]22 ,although it must be remembered that the father also contributes to the environment of the mother, economically and materially, in ways that may not be captured by relatively crude measures of SES. After adjusting for confounding factors, it was found that a LBW father was at a 2.2 times greater risk of begetting a LBW offspring than a father weighing >3000 g at birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are well-documented observations that birth weight is one of multiple etiological traits that are affected by environmental factors as well as the genetic disposition of the fetus and mother (Järvelin et al 1997;Klebanoff et al 1998;Knight et al 2005;Kramer 1987). The importance of genetic factors in determining birth weight was demonstrated by a twin and family study (Clausson et al 2000;Emanuel et al 1992;Klebanoff et al 1989;Magnus 1984). Many of the numerous birth weightassociated genes identified in previous studies are related to factors that affect non-insulin-dependent diabetes, such as mutations in the fetal insulin secretion reducing genes (e.g., INS, INSR, IPF1ABCC8, HNF1B), and these factors have been shown to have an effect on birth weight (Babenko et al 2006;Edghill et al 2006;Hattersley and Tooke 1999;Støy et al 2007).…”
Section: Introductionmentioning
confidence: 99%